2007
DOI: 10.1300/j137v15n02_06
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Leadership Development in African American Youth

Abstract: This exploratory study assesses factors related to leadership development for African American adolescents participating in a community service program designed to develop young African American leaders (N = 345). Psychometric characteristics of self-reported levels of leadership are explored to determine similarities and differences between gender groups. A multivariate analysis of socioeconomic factors, levels of self-esteem, school grades, and social activities as predictors of leadership development produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Studies have shown that having leadership skills is an important buffer against negative outcomes for minority youth (e.g., Shelton 2009; Teasley et al 2007). Although for white middle class youth, leadership ability may contribute to attaining higher social status and social influence (Mayeux et al 2008; Vaillancourt et al 2007), research examining popularity and aggression as they relate to leadership among urban youth is scarce (Brechwald and Prinstein 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that having leadership skills is an important buffer against negative outcomes for minority youth (e.g., Shelton 2009; Teasley et al 2007). Although for white middle class youth, leadership ability may contribute to attaining higher social status and social influence (Mayeux et al 2008; Vaillancourt et al 2007), research examining popularity and aggression as they relate to leadership among urban youth is scarce (Brechwald and Prinstein 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The programs identified in the review used a range of both qualitative and quantitative evaluation methods. Many studies employed interviews with participants (n = 22) (Brown and Albert 2015;Christens and Dolan 2011;Dima and Bucuta 2020;Franzen et al 2009;Gullan et al 2013;Halsall and Forneris 2018;Harvey et al 2021;Ile and Boadu 2018;Levy 2012;McNae 2010;Owen and Irion-Groth 2020;Parkhill et al 2018;Pearrow 2008;Pink et al 2020;Quinn and Nguyen 2017;Sisselman-Borgia 2021;Stedman et al 2009;Taylor 2016;Zimmerman et al 2011) or surveys (n = 11) (Franzen et al 2009;Mazurek Melnyk et al 2007;Moody et al 2003;Morrel-Samuels et al 2018;Redivo and Buckman 2004;Sewell et al 2020;Sisselman-Borgia 2021;Taylor 2016;Thomas and Mcadoo 2008;Thorpe 2007;Zimmerman et al 2011), while others used scales (n = 9) (Crave and El Sawi 2001;Grenwelge 2010;Teasley et al 2007;Zimmerman et al 2011), including the youth leadership life skills developmental scale (Ahrens et al 2015;Puxley and Chapin 2020), the individual protective factors index (Berlin et al 2007), a program session satisfaction scale…”
Section: Program Evaluationmentioning
confidence: 99%
“…Relatedly, a total of 12 empirical reviewed studies were organized concurrently in the four following parts: (a) There are more research findings explaining the relationship between leadership and self-concept development as it is interpreted as a social adjusting mechanism (Hickman, 2006; Hollar, 2014; Li et al, 2011; Scharf & Mayseless, 2009; Teasley et al, 2007); (b) There are more studies dealing leadership with both environmental support and innate capacities (Atwater et al, 1999; Avolio, 2005; Bass & Bass, 2008; Day, 2000; DeRue & Wellman, 2009, cited in Li et al, 2011, p. 111); (c) There are increasing number of studies indicating the significant of systematic practical support (Sun et al, 2017; Turgunbaeva et al, 2017) and social emotional support (Guerin et al, 2011; Hickman, 2006; Li et al, 2011; Rivizzigno et al, 2014; Scharf & Mayseless, 2009; Teasley et al, 2007); (d) There are escalating number of studies viewing children's leadership development process as a their personality growth process (Guerin et al, 2011; Hickman, 2006; Li et al, 2011; Rivizzigno et al, 2014). Relatively, prosocial-leadership development is understood as the optimum for children's leadership development.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reviewed leadership-related studies collectively suggest that personality-focused leadership development can promote tweens’ prosocial leadership that is strongly related to their positive self-concept development. (Guerin et al, 2011; Hickman, 2006; Li et al, 2011; Liebenberg & Roos, 2008; Rivizzigno et al, 2014; Scharf & Mayseless, 2009; Teasley et al, 2007).…”
Section: Introductionmentioning
confidence: 99%